Nemzetállam-építés eszközei az első Csehszlovák Köztársaságban - Simon, Attila (Közép-Európai Közlemények, 2009)
The Czech Republic between the two world wars is described by the Czech and Slovak historians as the most democratic state in Central-Europe. Some of the Hungarian historians still adopt this statement without doubts. Our paper analyzes this issue with criticism, showing the shortcomings of Czechoslovakian democracy. The most important of these shortcomings is that the Czechoslovakian democracy was not democratic towards the minorities, it was oppressing them.